Focal vascular occlusion: A link between livedoid vasculopathy and cutaneous arteritis? - Géza R. Nagy; Klára Veres; Nóra Belső; István Balázs Németh; Erika Varga; Irma Korom; Lajos Kemény; Zsuzsanna Bata‐Csörgő (Wiley, 2023)
Abstract Background Livedoid vasculopathy (LV) and cutaneous arteritis (CA) are rare cutaneous diseases. A consideration of these two conditions as different entities is debatable, because thrombosis and inflammation are closely related in their pathogenesis mechanisms. Varying reports on the effectiveness of anticoagulant and immunosuppressant therapies in LV and CA also point to diagnostic challenge and overlap in these conditions. Objectives We sought to assess the therapeutic effect of anticoagulation therapy in adult patients with CA, who were recalcitrant to immunosuppressive modalities. Methods A monocentric retrospective analysis of adult patients who were diagnosed with CA between 2010 and 2018, was carried out. Results We describe 8 cases of long‐term recalcitrant CA, in whom anticoagulation therapy significantly reduced the pain and cutaneous symptoms. All patients had cutaneous symptoms compatible with CA along with clinical features also characteristic of LV, including underlying procoagulative disorders in the majority (87.5%), as confirmed by screening for thrombophilia. We also review current concepts regarding LV and CA, and suggest vascular occlusion is a common link between these two entities. Conclusions Although current knowledge advocates segregating vasculopathy from vasculitis by means of histopathological examination in LV and CA, clinical experience suggests some overlap and common complex underlying pathomechanisms.